1994
DOI: 10.1002/app.1994.070530306
|View full text |Cite
|
Sign up to set email alerts
|

EVA–EPDM blends as cable insulant

Abstract: SYNOPSISBase materials for heat-resistant cable insulant have been developed from blends of ethylene vinyl acetate (EVA) copolymer containing 28% VA and ethylene propylene diene (EPDM) rubber. Different electrical, mechanical, and thermal properties of these blends have been studied extensively. Aging under different conditions has also been studied. The chemical and mechanical stability of these compositions has been assessed at the actual temperature range of application. Dielectric properties have been dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…Detailed studies on the relationship between morphology of LDPE/EVA blends and their mechanical properties, dynamic mechanical properties and electrical resistance have been reported. [21][22][23][24][25][26] Ray and Khastgir [22] found that an interpenetrating polymer network-like structure was formed in LDPE/EVA blends with a minimum content of 50 wt.-% EVA. Up to now no information has been reported on the ESCR behavior of LDPE/EVA blends.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed studies on the relationship between morphology of LDPE/EVA blends and their mechanical properties, dynamic mechanical properties and electrical resistance have been reported. [21][22][23][24][25][26] Ray and Khastgir [22] found that an interpenetrating polymer network-like structure was formed in LDPE/EVA blends with a minimum content of 50 wt.-% EVA. Up to now no information has been reported on the ESCR behavior of LDPE/EVA blends.…”
Section: Resultsmentioning
confidence: 99%
“…1 Blend (EVA/EPDM) had partial miscibility in the amorphous region. 2 Dicumyl peroxide (DCP) was used as an initiator in cross-linking EVA/EPDM over the entire range of composition. 3 Consequently, miscibility and mechanical properties of EVA/EPDM were improved.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Earlier studies on accelerated ageing of rubber vulcanizates show that the properties such as elongation at break, tensile strength, and modulus undergo changes due to deterioration. 6 It is well known that for many unsaturated rubbers, the hydrogen atom of a-methylenic carbon is abstracted in the presence of oxygen and an oxidative reaction chain is initiated which propagates auto-catalytically and ends in chain scission. Besides scission of the main chain and of the cross-links, depending upon polymers, ageing causes the formation of more cross-links of the same type as those already present or of a different type, which may be inactive to further scission.…”
Section: Introductionmentioning
confidence: 99%